2021
DOI: 10.1002/1878-0261.12893
|View full text |Cite
|
Sign up to set email alerts
|

CircATRNL1 activates Smad4 signaling to inhibit angiogenesis and ovarian cancer metastasis via miR‐378

Abstract: Ovarian cancer is one of the most frequent carcinomas in females, and the occurrence rate is still rising despite many advances made. The pathogenesis of ovarian cancer remains greatly unclear. Here, we investigated the mechanisms of ovarian cancer, with the focus on circATRNL1. Human ovarian cancer tissues and cell lines were used to examine levels of circATRNL1, miR‐378, Smad4, AKT, and other proliferation‐related and migration‐related proteins. Cellular assays were used to determine cancer cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…None of the other three circRNAs (circFAT3, circATRNL1, and circITGA7) have been functionally linked to PC or described in expression studies in PC patient samples. However, both circITGA7 and circATRNL1 have been described as downregulated in other cancers, including colorectal cancer (CRC) (circITGA7, [ 34 , 35 ]) and ovarian cancer (circATRNL1, [ 36 ]), similar to our findings in PC. Moreover, circITGA7 and circATRNL1 have been reported to be involved in cell proliferation, invasion, and migration in CRC and ovarian cancer [ 34 , 36 ], supporting a potential functional role of these circRNA candidates in cancer development/progression.…”
Section: Discussionsupporting
confidence: 89%
“…None of the other three circRNAs (circFAT3, circATRNL1, and circITGA7) have been functionally linked to PC or described in expression studies in PC patient samples. However, both circITGA7 and circATRNL1 have been described as downregulated in other cancers, including colorectal cancer (CRC) (circITGA7, [ 34 , 35 ]) and ovarian cancer (circATRNL1, [ 36 ]), similar to our findings in PC. Moreover, circITGA7 and circATRNL1 have been reported to be involved in cell proliferation, invasion, and migration in CRC and ovarian cancer [ 34 , 36 ], supporting a potential functional role of these circRNA candidates in cancer development/progression.…”
Section: Discussionsupporting
confidence: 89%
“…At present, seven studies have explored the roles of circATRNL1 ( Zhang et al, 2019a ; Wang et al, 2020a ; Chen et al, 2020 ; Wang et al, 2021a ; Wang et al, 2021b ; Zhang et al, 2021c ; Zheng et al, 2021 ), but three did not include has_circ_0020093 ( Chen et al, 2020 ; Wang et al, 2021b ; Zhang et al, 2021c ). In a study by Wang et al, circATRNL1 activated Smad4 signaling and suppressed angiogenesis and ovarian cancer metastasis by binding miR-378 ( Wang et al, 2021a ). Zhang et al found that circATRNL1 was downregulated in women with polycystic ovary syndrome ( Zhang et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Izeradjene et al [ 57 ] revealed that the formation of mucinous cystic neoplasms is induced by synergistic effects of Kras-G12D and Smad4 mutations. The role of Smad4 in other human cancers, such as colorectal cancer (CRC)[ 58 ], gastric cancer[ 59 ], ovarian cancer[ 60 ] and head and neck squamous cell carcinoma (HNSCC)[ 61 ], is similar to that in pancreatic cancer. Downregulation of Smad4 is considered an early event of HNSCC, which is different from pancreatic cancer.…”
Section: Multiple Roles Of Smad4 In Tumorigenesismentioning
confidence: 99%